Persepsi Dosen Program Studi Pendidikan Biologi terhadap Integrasi dan Implementasi Komponen Literasi Saintifik dalam Desain Kurikulum - Maulidia, Lailil; Suwono, Hadi; Furaidah, Furaidah (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This study aims to determine the perception of lecturers of Biology Education Program on the integration of scientific literacy on curriculum design. The data were collected by questionnaire consisting of four dimensions: (1) curriculum component, (2) development of teaching staff, (3) curriculum development and evaluation, and (4) resources. The results show that scientific literature is integrated in the curriculum component but the lecturer considers science as simply the material being taught. In addition training, access to aid, and awards for teachers who undertake scientific literacy learning are lacking. For lecturers, the availability of standard instruments and the regularity of curriculum evaluation also need to be accommodated.Abstrak: Penelitian ini bertujuan untuk mengetahui persepsi dosen prodi Pendidikan Biologi mengenai integrasi literasi saintifik pada desain kurikulum. Pengambilan data dilakukan dengan kuesioner yang terdiri dari empat dimensi yakni (1) komponen kurikulum, (2) pengembangan tenaga pengajar, (3) pengembangan dan evaluasi kurikulum, dan (4) sumber daya. Hasil menunjukkan bahwa literasi saintifik terintegrasi dalam komponen kurikulum namun dosen menganggap sains sekedar materi yang diajarkan. Selain itu, pelatihan, akses bantuan, dan penghargaan bagi pengajar yang melakukan pembelajaran literasi saintifik masih kurang. Bagi dosen, ketersediaan instrumen baku dan keteraturan evaluasi kurikulum juga perlu untuk diakomodasi.